The effect of artificial dehydration on the survival and reproduction of Lymnaea rubiginosa - S Widjajanti (Indonesian Center for Animal Research and Development (ICARD), 1999)
The effect of artificial dehydration on snail Lymnaea rubiginosa was investigated in the laboratory by monitoring its survival and development, because as aquatic organism, this snail must be able to adapt or tolerate with the changes in its habitat. Fifty laboratory-reared L. rubiginosa with shell length between 1.0-1.5 cm (adult) were placed in each sloping earth aquarium (60x80x20 cm) which were already filled with water about 15 cm depth. Five aquaria were used in this study, and one week after being established the water from 4 aquaria was drained while one aquarium was retained with water as a control. The water was replaced in one of dehydrated aquarium each week for four weeks, commencing one week after draining the water. The survival of snails in each aquarium were recorded every two days over a period of 3 months. The results indicated that the mortality rate of adult snails increased as the period of dehydration increased. After four week dehydration only 16% of adult snails survive compared to 68% survival in the control aquarium, and dehydration for 4 weeks prolonged the hatching time of eggs. Moreover, in dehydrated aquaria, the egg masses were deposited in a random pattern on the surface of the soil, whereas in the control aquarium they were laid on the soil-water junction. Key words : Dehydration, Lymnaea rubiginosa, survival, fasciolosis